1531. Antibiotic Selection for Neisseria gonorrhoeae among Penicillin Allergic Patients in the Emergency Department - McGuinness, Matthew J (Open Forum Infect Dis, 2020)
BACKGROUND: While penicillin (PCN) allergies are commonly reported, their cross-reactivity with beta-lactam antibiotics is minimal. First line treatment of gonorrheal infections includes a cephalosporin (CPH). In an emergency department (ED) environment, physicians must consider potential allergies when selecting antibiotics for a patient with symptoms concerning for sexually transmitted infection (STI). METHODS: A retrospective chart review on adult patients with symptoms concerning for STI presenting to an urban ED from January 2014 through June 2019 was performed. Chart discovery was performed using search terms of “STI”, “STD”, “urethritis”, “vaginitis”, and “gonorrhea”. Information abstracted included patient symptoms, type of care provider, and antibiotics prescribed or administered in the ED. The primary outcome was prevalence of allergy to PCN and CPH in patients evaluated for STI symptoms and secondary outcomes included prescribed antibiotic treatments. Chi-square and Fischer-exact tests were utilized to examine for statistical significance, with p values < 0.05 as statistically significant. RESULTS: A total of 603 patients met the inclusion criteria, of which 31 reported allergies to PCN, and another 3 reported allergies to CPH. Patients reporting PCN allergy were found to be less likely to receive a CPH antibiotic (p=0.0035). Patients reporting a non-anaphylactic allergy to PCN received a CPH at a rate of 92.3%. Attending physicians in particular were less likely to prescribe a CPH antibiotic to a patient reporting allergy compared with both resident physicians and PAs (p=0.00019). Patients reporting a PCN allergy were more likely to receive alternative antibiotics beyond CPH or azithromycin (p=0.046); the most frequently given antibiotics were metronidazole, doxycycline, and levofloxacin. Demographic Data [Image: see text] Antibiotic Prescriptions by Type of Penicillin Allergy [Image: see text] Antibiotic Prescriptions for Penicillin Allergy vs. No Allergy [Image: see text] CONCLUSION: Patients with PCN allergies represent a recurring challenge for ED physicians when faced with antibiotic selection for STI symptoms concerning for gonorrheal infection. Those with PCN allergies are significantly less likely to receive a CPH antibiotic, though these remain the only universal treatment for gonorrheal infections. These findings highlight the significant need for further physician education on allergies and antibiotic selection. DISCLOSURES: All Authors: No reported disclosures